(untitled) - Food and Agriculture Organization of the United Nations (Bangkok, 2011)
This is the twenty-seventh issue of the above publication, a comprehensive and detailed compilation of statistics on farming, livestock, fishery, forestry and nutrition in Asia-Pacific countries for the decade 2000-2010. Statistics are listed separately for developing countries (including transition economies) and developed countries in the region. The publication uses mostly FAO statistics based on information provided by member countries. Included is a section on country profiles and two tables reporting on the status of organic farming and the production and trade of biofuels in the region. The publication provides a handy comparison of changes over the past decade in the use of agricultural land and farm inputs, production of farm and horticulture crops, livestock, fisheries, forestry and agricultural trade in countries of the Asia-Pacific region, where about half of the total population is engaged in farming and related activities.
Keywords: Agricultural products,Sản phẩm nông nghiệp